Long-Term clinical outcomes of subcutaneous implantable defibrillator therapy in patients with heart failure and reduced ejection fraction: a single center experience. (24th May 2021) - Ben Kilani, M; Jacon, P; Carabelli, A; Venier, S; Defaye, P
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): P. JACON consultant: Boston Scientific France Introduction: The implantable cardioverter defibrillator (ICD) is the most effective therapy for prevention of sudden cardiac death in high-risk patients with heart failure and reduced ejection fraction (HFrEF). The subcutaneous implantable cardioverter defibrillator (S-ICD) has been considered as a comparable and relatively safer alternative to transvenous ICD in patients (pts) without pacing indication. Purpose: Our aim was to assess the clinical "real-life" outcomes of S-ICD in patients with HFrEF and primary or secondary prevention, over a long-term follow-up (FU) period after S-ICD implantation. Methods: All pts with HFrEF (left ventricular ejection fraction ≤35%) implanted with a S-ICD and a FU above 6 months were included in a cross-sectional monocentric study. Pts were followed by remote monitoring. Results: 88 pts were included (52 ± 12.8 years old, male 87.5%). Indications were: primary 92% and secondary 8% prevention  (ischemic cardiopathy 46%; dilated 46%; hypertrophic 5%; congenital 2%; valvular 1%). The mean left ventricular ejection fraction was 27%. 9 pts had a previous transvenous ICD implanted, but required revision because of infection or lead defects. The mean FU period was 33 ± 18 months with a mortality rate of 10% (S-ICD-related death secondary to inappropriate (inap) shocks for one patient). 5 pts underwent S-ICD system extraction after a mean FU period of 30 ± 21 months. Reasons were infectious complication (1 pt), pacing indication (2 pts) and S-ICD lead dysfunction (2 pts). Extraction after heart transplant was performed in 4 pts. During FU, 18 pts (20.5%) experienced at least one therapy: 8 pts (9%) with appropriate (ap) (3.3% per year) and 11 pts (12%) with inap shocks (4.36% per year). A total number of 24 ap shocks have been observed (3 ± 4 ap shocks per patient, several shocks for 3 pts), the first shock occurred after a mean FU period of 24 ± 14 months. 2 pts were referred to VT ablation and no recurrence of events was observed after medical therapy modification for the other pts. For the 11 pts with inap shocks, time to the first event was 19 ± 20 months. Reasons were: supraventricular arrhythmias (18%), T wave (36%) and noise (54%) oversensing. There was 1.8 ± 1.6 shock per patient with several shocks for 4 pts. Among pts with inap shocks, 2 pts required S-ICD system extraction, 1 pt died, while reprogramming and medical therapy options were efficient in other pts. Conclusion: In pts with HFrEF at high risk of sudden cardiac death, S-ICD has proven to be effective in treating ventricular arrhythmias. However, more investigations must be conducted to explain the real-life high rate of inappropriate therapies.